Evaluation of migration decision-selectivity factors in metropolitan area: a case of Klang Valley region, Malaysia - Mohd Fadzil Abdul Rashid,; Ishak Ab. Ghani,; Ibrahim Ngah,; Suziana Mat Yasin, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2014)
Internal migration is one of the important spatial phenomena in urban areas that contributes to high level of urban growth and urbanisation. Accordingly, it leads to crucial effects on social, economic and physical developments in urban areas. Hence, understanding of spatial trends and distribution of migration in urban areas is crucial for the purpose of urban planning decision making. This paper focuses to identify and evaluate relative importance of migration decision-selectivity factors that affect the spatial distribution of migration in metropolitan area. The analysis is based on migration behavioural survey in the Klang Valley region, Malaysia. The results of analysis show that factors from spatial-economic aspect influence distribution of migration the most in the Klang Valley. The factor of the highest importance index is affordable housing areas, followed by new residential areas, the acceptable cost of living, nearness to place of work, and good physical and environmental features. Then, it is followed by spatial-social factors such as good social and community living. Finally, this paper concludes that the determinant migration decision-selectivity factors will help urban planners to understand spatial distribution of migration potential in urban areas in order to plan a proper development planning for the future.